Control interno y su incidencia en la eficacia y eficiencia en la gestión de inventario del almacén “Calzado Patricia”, Cantón El Empalme, año 2023 - Moncayo Rodríguez , Rosa Maribel (2024)
This research addresses a problem of vital importance for marketing companies, it allowed investigating how an adequate internal inventory control can collaborate in the efficient optimization of all the resources stored in the warehouses, ensuring an effective administration and management. In addition, an adequate inventory management allows to identify with precision the products with higher and lower rotation, which results in the reduction of costs associated with excessive maintenance of merchandise, and also avoids the loss of customers caused by a limited inventory that prevents the availability of products at the time they are requested by the customer. The objective of the research is to evaluate how internal control affects the effectiveness and efficiency of warehouse inventory management. The techniques used were direct observation, interviews with the owners and evaluation of the internal control through a questionnaire of questions related to the inventory area. The inductive, deductive, analytical and historical-logical method was used to gather information that would allow us to vary sales and determine the factors that influence the increase or decrease of sales. The results revealed significant deficiencies in inventory management, with a control risk of 46% and an inherent risk of 56%. These deficiencies are attributed to a lack of accuracy in physical inventory, making purchases without adequate planning, a low level of inventory turnover, and the absence of a scheme specifying responsibilities and roles within the organizational structure. Key word: Internal Control, Management, Inventory, effectiveness, efficiency.